Drug Excipient Interaction Studies in Dopamine Loaded Lipid- Surfactant Based Drug Carrier - Mishra, Manisha; Ravichandran, N.; Pichandy, Muthuprasanna (Asian Journal of Chemistry, 2011)
In present study, chemical and physical interaction studies were carried out between the drug dopamine HCl with lipids (cholesterol, lecithin) and surfactants (Span 20, 40, 80) and Tween 80 excipents. These excipients were an important constituent in designing liposomal drug delivery. Fourier transform infrared spectroscopical studies (FTIR) of drug showed no deviation in characteristic drug absorption peaks in presence of formulating excipients. O-H (Hydroxyl) and N-H (amine group) stretching vibrations and C-H bending vibrations (methyl group) of drug was prominent in both drug and with excipients. This explicitly showed absence of interference in eliciting drug's pharmacodynamic properties. Differential scanning calorimetric study were also performed to determine the physical interaction among the drug, lipid and surfactant excipients. The liposomal formulations with and without surfactants showed complete absence of those pure lecithin endothermic peaks particularly its melting point peak. Other characteristic peaks of lecithin appears shifted to about 5-8 ºC which indicates fluidization during the formation of lipid bilayers. The lecithin and cholesterol peak of surfactant liposomes showed very less or broad endothermic peak which is an indicative that surfactant have interacted well with the lipids during the formation of vesicles. Conversion of crystalline dopamine drug to amorphous was also proved in the differential scanning calorimetric studies.